Antibiotic resistant pseudomonas SP. biomigi protects susceptible bacteria from disinfectants - Gül, Gökçin. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2016., 2016)
Benzalkonium chlorides (BACs), are one of the biocides that are active ingredients of many disinfectants. A novel bacteria Pseudomonas sp. BIOMIG1 which is resistant to BACs and degrade BACs at high concentrations has recently been isolated. The objective of this research is to evaluate antibiotic resistance of BIOMIG1 and elucidate the impact of BIOMIG1 on the efficacy of BAC containing disinfectants. Tolerance of BIOMIG1s, E. coli and Serratia marcescens against 18 antibiotics was measured by using macro dilution and E-test methods. BAC resistant bacteria were more resistant to tested antibiotics than BAC susceptible bacteria which suggested that BAC resistance favor antibiotic resistance. Antibiotic biodegradation potential was tested in shake-flasks. While BIOMIG1 did not biodegrade antibiotics, Serratia marcescens degraded amoxicillin and penicillin g. Lastly, BAC susceptibility of E.coli, in the presence of BIOMIG1 in co-culture was investigated. Domestos® was used as BAC source. Experiments were performed in liquid medium. While E. coli alone was survived up to 4 mg/L initial BAC, it survived at up to 125 mg/L initial BAC in co-culture which suggested that BIOMIG1 protect E. coli from disinfectant.
Keywords: Benzalkonium chloride.; Pseudomonas.